An electronic, unsupervised patient-reported Expanded Disability Status Scale for multiple sclerosis. (August 2021) - Romeo, Andrew R; Rowles, William M; Schleimer, Erica S; Barba, Patrick; Hsu, Wan-Yu; Gomez, Refujia; Santaniello, Adam; Zhao, Chao; Pearce, Jennifer R; Jones, JB; Cree, Bruce C; Hauser, Stephen L; et al.
Background: In persons with multiple sclerosis (MS), the Expanded Disability Status Scale (EDSS) is the criterion standard for assessing disability, but its in-person nature constrains patient participation in research and clinical assessments. Objective: The aim of this study was to develop and validate a scalable, electronic, unsupervised patient-reported EDSS (ePR-EDSS) that would capture MS-related disability across the spectrum of severity. Methods: We enrolled 136 adult MS patients, split into a preliminary testing Cohort 1 ( n  = 50), and a validation Cohort 2 ( n  = 86), which was evenly distributed across EDSS groups. Each patient completed an ePR-EDSS either immediately before or after a MS clinician's Neurostatus EDSS evaluation. Results: In Cohort 2, mean age was 50.6 years (range = 26–80) and median EDSS was 3.5 (interquartile range (IQR) = [1.5, 5.5]). The ePR-EDSS and EDSS agreed within 1-point for 86% of examinations; kappa for agreement within 1-point was 0.85 ( p  < 0.001). The correlation coefficient between the two measures was 0.91 (<0.001). Discussion: The ePR-EDSS was highly correlated with EDSS, with good agreement even at lower EDSS levels. For clinical care, the ePR-EDSS could enable the longitudinal monitoring of a patient's disability. For research, it provides a valid and rapid measure across the entire spectrum of disability and permits broader participation with fewer in-person assessments.